OC-068 Structure and function of the gastro-oesophageal junction in patients after laparoscopic fundoplication: concurrent magnetic resonance imaging and high-resolution manometry studies. (23rd September 2015) - Fox, M R; Kaufman, E; Curcic, J; Wyss, M; Schneider, P; Fried, M; Bösiger, P; Schwizer, W
Abstract : Introduction: Laparoscopic fundoplication provides effective reflux control in patients with gastro-oesophageal reflux disease (GERD); however a proportion of patients that undergo surgery experience troublesome symptoms. Improved results may be possible if more was known about the structural factors that effect treatment outcome. This study applied concurrent MRI and HRM technology to compare the structure and function of the GEJ in GERD patients after fundoplication to control groups of GERD patients and healthy participants (HPs). Methods: Eight GERD patients were studied at least 3 months after laparoscopic fundoplication with subjectively good treatment outcome (7M, age 18–67 years). Results of pH-impedance monitoring off acid suppression before and after fundoplication were available. 12 patients with GERD on medical therapy (7M, age 20–55 years) and 12 HPs (7M, age 26–36 years) with no history of gastro-intestinal disease or surgery. Validated MRI measurements of the oesophago-gastric insertion angle (Radiology in press) and gastric volumes were performed at baseline and after ingestion of high calorie meal (McDonalds Cheeseburger, Chips, Milkshake, 735 kcal). Visual Analogue Scales (100 mm VAS) documented dyspeptic symptoms. Results: GEJ pressure increased from before to after fundoplication (8.3±1.2 vs 14.2±1.7 mm Hg, p=0.03) whereas acid exposure (10.3±2.2 vs 5.4±2.1, p=0.001) and reflux episodes reduced (39±3 vs 24±2, p=0.019). The insertion angle after the meal was more obtuse after surgery than in the disease and healthy controls (61° vs 48° vs 41°, p<0.008). Moreover normal variation of insertion angle with respiration was lost. Postprandial gastric air content was higher after fundoplication compared to the disease and healthy controls in absolute terms (523 vs 146 vs 178 ml, p<0.001) and as a proportion of total gastric content (78% vs 12% vs 16%, p<0.005). There was a positive correlation between insertion angle and gastric air content (r2=0.95, p=0.050). Postprandial abdominal bloating was higher for the fundoplication group compared to the GERD and healthy groups. (VAS 55±21 vs 13±23 vs 20±10 mm, p=0.049) and there was also an association between gastric air content and the this symptom (r2=0.82, p=0.07). Conclusion: Novel, quantitative MRI measurements demonstrate alterations to GEJ structure after fundoplication, specifically to the oesophago-gastric insertion angle, that are linked to gastric retention of air and the sensation of bloating, even in patients with a good subjective outcome. Modification of surgical technique to restore more normal GEJ morphology may be equally effective for reflux protection but cause less troublesome bloating.